Explaining the emergence of team agility: a complex adaptive systems perspective. Issue 3 (8th May 2018) - Werder, Karl; Maedche, Alexander
Abstract : Purpose: Agile software development helps software producing organizations to respond to manifold challenges. While prior research focused on agility as a project or process phenomenon, the authors suggest that agility is an emergent phenomenon on the team level. The paper aims to discuss this issue. Design/methodology/approach: Using the theory of complex adaptive systems (CASs), the study captures the multiple influencing levels of software development teams (SDTs) and their interplay with self-organization and emergence. The authors investigate three agile SDTs in different contextual environments that participate with four or more different roles each. Findings: The results suggest self-organization as a central process when understanding team agility. While contextual factors often provide restriction on self-organization, they can help the team to enhance its autonomy. Research limitations/implications: The theoretical contributions result from the development and test of theory grounded propositions and the investigation of mature agile development teams. Practical implications: The findings help practitioners to improve the cost-effectiveness ratio of their team's operations. Originality/value: The study provides empirical evidence for the emergence of team agility in agile SDTs. Using the lens of CAS, the study suggests the importance of the team's autonomy.